Cryptography engineering : design principles and practical applications - Ferguson, Niels; Kohno, Tadayoshi; Schneier, Bruce , 1963- (Wiley, 2010)
Cryptography is vital to keeping information safe, in an era when the formula to do so becomes more and more challenging. This book shows you how to build cryptography into products from the start